2018
DOI: 10.1016/j.surfcoat.2018.01.073
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and microstructural characterization of MCrAlY coatings produced by laser cladding: The influence of the Ni, Co and Al content

Abstract: Laser metal deposition (LMD) and laser cladding (LC) are alternative methods to thermal spraying processes to produce dense, high-quality coats. In this work, two MCrAlY coatings (M=Ni+Co) have been prepared onto stainless substrate using a coaxial LC technique under two different Ni/Co and Al proportions. The mechanical properties were then evaluated with microhardness, nanoindentation, and three-point bending tests. The microstructure and composition of coatings were characterized by X-Ray Diffraction (XRD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…Energies 2022, 15,1914 16 of 45 eters is of utmost importance in obtaining a high-quality continuous coating and preventing common material defects, including cracks, pores and lack of fusion [143]. As mentioned earlier (Figure 1), the coating/substrate adhesion is one of the major characteristics of a suitable coating, which fulfils the function of protecting against tribological failures at high temperatures.…”
Section: Laser Claddingmentioning
confidence: 98%
See 1 more Smart Citation
“…Energies 2022, 15,1914 16 of 45 eters is of utmost importance in obtaining a high-quality continuous coating and preventing common material defects, including cracks, pores and lack of fusion [143]. As mentioned earlier (Figure 1), the coating/substrate adhesion is one of the major characteristics of a suitable coating, which fulfils the function of protecting against tribological failures at high temperatures.…”
Section: Laser Claddingmentioning
confidence: 98%
“…Specifically, the coaxial laser-cladding process has been successfully tested to manufacture dense coatings by using a special nozzle head, which provides the overlapped individual laser tracks [142]. It is worth noting that controlling the process parameters is of utmost importance in obtaining a high-quality continuous coating and preventing common material defects, including cracks, pores and lack of fusion [143]. As mentioned earlier (Figure 1), the coating/substrate adhesion is one of the major characteristics of a suitable coating, which fulfils the function of protecting against tribological failures at high temperatures.…”
Section: Laser Claddingmentioning
confidence: 99%
“…O autor [27] comprovou que as zonas ricas em Y são distribuídas aleatoriamente, mas sempre em torno dos contornos dos grãos ou em torno de pequenas porosidades na camada quando estudou rotas de processamento a laser de NiCoCrAlY sobre AISI 304. E outros autores [28] também identificam óxidos de ítrio na superfície de NiCrAlY ao estudar ciclos de oxidação do Hastelloy X com revestimento de NiCrAlY via laser.…”
Section: Agradecimentosunclassified
“…They found that a high dilution can lead to a high HAZ. Pereira et al [16] observed that during laser cladding of NiCoCrBSi on stainless steel, a very low dilution zone (metallurgical method) at about 2 μm is enough to obtain a perfect bonding without affecting the substrate mechanical properties (no cracking behavior observed). Many authors [17][18] presented an EDS analysis to measure the dilution between two materials and its components' chemical evolution.…”
Section: Introductionmentioning
confidence: 99%